2022
DOI: 10.1097/pas.0000000000001981
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Tumors Resembling Ovarian Sex Cord Tumors

Abstract: Uterine tumors resembling ovarian sex cord tumors (UTROSCTs), first characterized by Drs Clement and Scully in 1976, are rare neoplasms showing clinical, morphologic, and immunohistochemical overlap with a number of other uterine tumors, most being mesenchymal. Criteria for aggressive behavior are not clearly established. We report 75 tumors from patients ranging from 21 to 84 (mean=52.4) years. Seventy-one patients were treated by hysterectomy and 4 by conservative total excision. Thirty-eight tumors were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 55 publications
0
41
2
Order By: Relevance
“…38,39 There was no expression of HMB45 in 9 UTROSCT cases in the literature 36 and no expression of melanocytic markers (11 of Melanin-A and 2 of HMB45) in our series, though occasionally Melanin-A was expressed in the individual case. 11,36 Therefore, comprehensive morphological observation and polyphenotypic immunohistochemical profile are important for differential diagnosis of UTROSCTs. However, molecular detection is preferred for those cases with overlapping morphology features.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…38,39 There was no expression of HMB45 in 9 UTROSCT cases in the literature 36 and no expression of melanocytic markers (11 of Melanin-A and 2 of HMB45) in our series, though occasionally Melanin-A was expressed in the individual case. 11,36 Therefore, comprehensive morphological observation and polyphenotypic immunohistochemical profile are important for differential diagnosis of UTROSCTs. However, molecular detection is preferred for those cases with overlapping morphology features.…”
Section: Discussioncontrasting
confidence: 52%
“…It was recently reported that ESR1::NCOA2/3 rearrangement was also found in adenosarcoma with sex cord differentiation 35 . However, a biphasic growth pattern with phyllodes-like architecture and periglandular stromal condensation of adenosarcomas is absent in UTROSCTs 36 . The distinction from epithelioid smooth muscle tumors is challenging in our series, mainly due to the small proportion of indistinct sex cord differentiation in GREB1 -rearranged tumors.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations